Transient absorption spectroscopy studies on polythiophene-fullerene bulk heterojunction organic blend films sensitized with a low-bandgap polymer - Löslein, Heiko; Ameri, Tayebeh; Matt, Gebhard; Koppe, Markus; Egelhaaf, Hans J.; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Brabec, Christoph (Macromolecular Rapid Communications, 2013)
Recently, the concept of near-infrared sensitization is successfully employed to increase the light harvesting in large-bandgap polymer-based solar cells. To gain deeper insights into the operation mechanism of ternary organic solar cells, a comprehensive understanding of charge transfer-charge transport in ternary blends is a necessity. Herein, P3HT:PCPDTBT:PCBM ternary blend films are investigated by transient absorption spectroscopy. Hole transfer from PCPDTBT-positive polarons to P3HT in the P3HT:PCPDTBT:PCBM 0.9:0.1:1 blend film can be visualized. This process evolves within 140 ps and is discussed with respect to the proposed charge-generation mechanisms. Polythiophene-fullerene bulk heterojunction ternary blend films are investigated by transient absorption spectroscopy. Hole transfer from PCPDTBT-positive polarons to P3HT in the blend film can be visualized. This process evolves within 140 ps and is discussed with respect to the proposed charge-generation mechanisms. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.